Beyond traditional CBRN force protection - a future of CBRN hardened super-soldiers? - David James Heslop (University of New South Wales, 2019)
Current momentum in military research efforts has opened the possibility for both the enhancement but also augmentation of military personnel for the purpose of achieving advantage over rivals. Rapid technological advances, currently breaking ground well ahead of prudent commentary and consideration of impacts on human society, ethics, geopolitics and military operations. This has potentially allowed friend and foe alike to exploit opportunities to develop completely novel countermeasures and defences, but also develop new threats in Chemical, Biological, Radiological and Nuclear (CBRN) military operations. In this editorial two recent technological developments driving medical countermeasure research are highlighted as examples. How such developments impact on capability competitions - in other words driving new arms races - in near-peer rivals is discussed. The profound potential impacts of these new technologies on the fundamentals of human existence as we understand it today are highlighted.